2019
DOI: 10.22319/rmcp.v10i4.4660
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento de materia seca y valor nutritivo de cuatro leguminosas herbáceas en la zona tropical de Hueytamalco, Puebla, México

Abstract: El objetivo del presente estudio fue evaluar el rendimiento de materia seca (MS), concentraciones de fibra detergente neutro y ácido (FDN y FDA), proteína cruda (PC) y digestibilidad in vitro de la MS (DIVMS) de las leguminosas forrajeras Stylosanthes guianensis (SG), Centrosema macrocarpum (CM), Pueraria phaseoloides (PP) y Arachis pintoi (AP). Durante 11 meses se realizaron seis cortes a intervalos de 56 días. La siembra de las especies se realizó en parcelas experimentales de 3 x 7 m bajo un diseño de bloqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
0
0
1
Order By: Relevance
“…This could be due to the loss of lower canopy leaves and the increase of stems, which have a higher percentage of cellulose, hemicellulose, and lignin, reducing the quality of the plant. Several researchers (Alonzo-Griffith and Paniagua-Alcaraz, 2010; Godoy-Espinoza et al, 2012;Romero et al, 2013;Portillo-López et al, 2019;Lagunes-Rivera et al, 2019) reported similar values in legumes, with protein percentages ranging from 28 to 14 % in the cutting stages from 30 to 75 days of age, respectively, with a behavior similar to that of this research; however, Balseca et al (2015) reported an average of 8.26 % PC in legumes, a lower result than this study. On the other hand, the planting density with the highest percentage of neutral detergent fiber (Table 3) was 50 000 plants ha -1 with 55 % (p < 0.05); the density with the lowest percentage was 200 000 plants ha -1 with 52 %.…”
Section: Resultssupporting
confidence: 79%
“…This could be due to the loss of lower canopy leaves and the increase of stems, which have a higher percentage of cellulose, hemicellulose, and lignin, reducing the quality of the plant. Several researchers (Alonzo-Griffith and Paniagua-Alcaraz, 2010; Godoy-Espinoza et al, 2012;Romero et al, 2013;Portillo-López et al, 2019;Lagunes-Rivera et al, 2019) reported similar values in legumes, with protein percentages ranging from 28 to 14 % in the cutting stages from 30 to 75 days of age, respectively, with a behavior similar to that of this research; however, Balseca et al (2015) reported an average of 8.26 % PC in legumes, a lower result than this study. On the other hand, the planting density with the highest percentage of neutral detergent fiber (Table 3) was 50 000 plants ha -1 with 55 % (p < 0.05); the density with the lowest percentage was 200 000 plants ha -1 with 52 %.…”
Section: Resultssupporting
confidence: 79%
“…Pero, aunque estos valores de las variables de la fibra, son altos comparados con los del presente estudio, mantienen la relación de valores bajos de A. pintoi y valores altos de las demás leguminosas. En un estudio de Lagunes-Rivera et al (2019), la especie A. pintoi tuvo menor contenido de fibras, contrastando con las demás leguminosas herbáceas que ellos estudiaron.…”
Section: Variables De La Fibraunclassified